More shade, better coffee - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Research suggests that growing coffee in tandem with trees improves the quality of coffee. Worldwide, coffee producers are suffering from low prices, with overproduction partly to blame. Countries such as Kenya and Brazil produce coffee in the full sun, a